PERINATAL TUBERCULOSIS WITH MILLIARY PATTERN IN INFANT AGED 28 DAYS - Savitri, Dian; Purniti, Putu Siadi; Kardana, Made (Medicina, 2014)
Perinatal tuberculosis (TB) was a very rare case. Its clinical manifestations could mimic bacterialinfection. The clinical course was often fulminant and characterized by dissemination and meningitis.Its mortality was very high, could achieve 100% in untreated patient. We reported a case of infant aged28 days admitted with breathlessness, fever, and poor feeding. Physical examination showedbreathlessness, pale, lethargy, and hepatomegaly. Chest radiograph showed a feature of milliary patternwith fine tubercles in both lung, supported with positive result on gastric aspirates for acid fast bacilli3 days respectively. Gastric aspirate culture for Mycobacterium tuberculosis showed positive result.Patient then diagnosed with perinatal TB with milliary pattern. This condition was accompanied withsevere sepsis and meningitis. Four TB regimens (isoniazid, rifampisin, pirazinamide, and ethambutol),corticosteroid, antibiotics were given. The patient was eventually died after receiving TB therapy for 13days. [MEDICINA 2014;45:208-212].